Spatial analysis of frost risk to determine viticulture suitability in Tasmania, Australia. (27th October 2017) - Webb, M.; Pirie, A.; Kidd, D.; Minasny, B.
Abstract: Background and Aims: New sites for viticulture should be located in areas where damaging spring frosts are less frequent and/or severe in order to remain economically viable. The aim of this study was to spatially determine frost risk at a high resolution (80 m) and develop new rules catered to viticultural suitability with respect to frost sensitivity for vines after budburst in spring across the state of Tasmania, Australia. Methods and Results: Frost risk was mapped for minimum temperature thresholds at −3, −2, −1, 0, 1 and 2°C using temperature values from 636 short‐term recording sites and linked to 57 Australian Bureau of Meteorology climate stations. Frost risk was spatially determined using regression tree interpolation and assessed against historical winegrape frost damage records garnered from survey information. Analysis indicated that the frost risk surfaces were accurate in portraying risk at the mesoclimate level and aligned well with grower expectations for frost risk modelled at ≤−1°C. Conclusions: Classifications of suitable, moderately suitable and unsuitable corresponding to <1 frost every 10 years (<10%), >1/10 to 1 frost every 2 years (10–50%) and 1 > frost every 2 years (>50%) for temperature values ≤−1°C was found to correlate well with viticulture suitability with regard to frost risk (after budburst) in Tasmania. Significance of the Study: This study presents a methodology for producing high‐resolution frost risk maps across large land areas that can accurately identify sites prone to damaging spring frosts and inform on new potential viticulture sites with suitability in mind.